Focusing on the big ideas: Non-biology science teachers learning experiences on biological evolution - Picardal, Marchee Tabotabo; Picardal, Jay Pajanustan (Jurnal Cakrawala Pendidikan, 2023)
Recognizing the ways teachers develop conceptual understanding of biological concepts bridges the gap between misconception and instruction. This descriptive phenomenology explored the learning experiences of eight non-biology major science teachers on evolution. Thematic analysis revealed six emergent themes: (a) First exposure was faulty and insufficient; (b) Lack of content knowledge leads to advanced studies; (c) Technology-supported learning resources facilitated learning process; (d) Rationalization of both old and new conceptions; (e) Application of concepts in different fields; and (f) Focusing on the big ideas. Overall, themes revealed that teachers developed a conceptual understanding of biological evolution through time and various means. Their adherence to the teleological beliefs leads them to experience confusion and misconceptions; however, as science teachers, they resolved the conflict to learning through content enrichment and professional development. A strong emphasis on the core principles of the Nature of Science and domains of biology in the curriculum across all levels and the teacher education program is imperative. Teachers can enhance their conceptual understanding and teaching efficacy through professional development and content enrichment.